2002
DOI: 10.1080/09544120220149250
|View full text |Cite
|
Sign up to set email alerts
|

Customization as a business strategy--a barrier to customer integration in product development?

Abstract: Although it is evident that product development (PD) within most companies does not take place in a vacuum, little is known about the in¯uence that other core company processes may have on the way PD activities are carried out. In the study presented in this paper, we focus on an analysis of the relationship between marketing strategies and the way customers are integrated in PD. An exploratory analysis of three medium sized companies acting in the interior design and the software industries (IT), represent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Earlier studies have identified risks in involving both suppliers [2] and customer [24,43] in product development. The representatives of the focal company did not stress the risks involved in dyadic collaboration with suppliers and customers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier studies have identified risks in involving both suppliers [2] and customer [24,43] in product development. The representatives of the focal company did not stress the risks involved in dyadic collaboration with suppliers and customers.…”
Section: Discussionmentioning
confidence: 99%
“…A customer is an important actor [19,21] affecting the whole supply chain. However, it has been found that engineering-oriented mindset highlighting sophisticated techniques instead of customer preferences is still perceivable in many companies providing customized offerings [24].This study highlights the increased effectiveness of product development as a result of collaboration across several companies; the focal company as the owner of product rights, its suppliers and customers. It aims to understand the drivers of interorganizational collaboration in the opening stages of product development projects.…”
mentioning
confidence: 89%
See 3 more Smart Citations